Near-field radiative heat transfer between two α-quartz plates having hyperbolic and double-negative-permittivity bands. (1st November 2022) - Su, Chengshuai; Fu, Ceji
Highlights: Demonstrated vast enhancement of NFRHT between α-quartz plates. Elucidated mechanisms for enhanced NFRHF in hyperbolic DNP bands. Quantified contributions to NFRHF by excited HVPhPs and HSPhPs for α-quartz. Revealed excitation of hyperbolic-like and elliptic-like SPhPs in DNP bands. Abstract: Near-field radiative heat transfer (NFRHT) between two semi-infinite α -quartz plates was theoretically investigated based on the fluctuation-dissipation theorem. By setting the temperatures of the two α -quartz plates respectively equal to 300 K and 299 K, the near-field radiative heat flux (NFRHF) was calculated and compared with the cases of SiC and hexagonal boron nitride (hBN), considering the influence of optic axis (OA) orientation. The results show that the NFRHF between the two α -quartz plates can surpass 3 times that between two SiC plates and 7 times that between two hBN plates at a separation distance of 10 nm. This vastly enhanced NFRHT was attributed to excitation of phonon polaritons in the hyperbolic and double-negative-permittivity (DNP) bands of α -quartz. It is found that excited surface phonon polaritons in DNP bands can be hyperbolic-like or elliptic-like, and the NFRHF in DNP bands contributes more than half of the total NFRHF for α -quartz. Furthermore, the hyperbolic and DNP bands that distribute in a wide frequency range give α -quartz the potential to achieve much higher NFRHF than using other materials such as SiC and hBN at different temperatures. Therefore, our work is helpful to deepen the understanding of surface polaritons in hyperbolic and DNP bands and their effect on NFRHT, which may be beneficial to design of energy transfer and conversion devices based on NFRHT.